Desain Sistem Pemasaran Produk UMKM dengan Konsep UI/UX Menggunakan Metode Design Thinking - Bebi Oktaviani; Reski Mai Chandra; Muhammad Irsyad; Pizaini Pizaini (Journal of Information System Research (JOSH), 2023)
The contribution of UMKM to the Indonesian economy has a major role in increasing economic growth in Indonesia. The development of UMKM in Indonesia has always been a special concern of many Indonesian citizens, including the government itself. Therefore, we conducted this research with the hope that the resulting product can provide solutions according to the needs and desires of users. This research focuses on system development for marketing UMKM products by designing UI and UX using the Design Thinking method. This Design Thinking method is a comprehensive thinking process that focuses on finding solutions with an empathetic process for a particular human-centered need. This method has 5 stages, namely Empathize, Define, Ideate, Prototype, and Testing. The testing method used is the SUS (System Usability Scale) method. System recommendations built in the form of a prototype using the Figma application. The feature that distinguishes this application from other applications is the AR feature to clearly see the product to be purchased. In addition, users can also choose souvenirs typical of an area by pressing directly from the interactive map provided. The prototype that was built was successfully tested on 10 respondents with an application prototype worth 87.